2019
DOI: 10.14283/jpad.2019.41
|View full text |Cite
|
Sign up to set email alerts
|

Multidomain Interventions to Prevent Cognitive Impairment, Alzheimer’s Disease, and Dementia: From Finger to World-Wide Fingers

Abstract: Alzheimer’s disease (AD) and dementia are a global public health priority, and prevention has been highlighted as a pivotal component in managing the dementia epidemic. Modifiable risk factors of dementia and AD include lifestyle-related factors, vascular and metabolic disorders, and psychosocial factors. Randomized controlled clinical trials (RCTs) are needed to clarify whether modifying such factors can prevent or postpone cognitive impairment and dementia in older adults. Given the complex, multifactorial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
116
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(120 citation statements)
references
References 59 publications
3
116
0
1
Order By: Relevance
“…Nonetheless, other interventions may have more subtle effects on amyloid burden, either directly or indirectly. Some examples would be BACE1 inhibitors [ 60 ], drugs with other targets which have downstream amyloid effects [ 61 ], or non-pharmacological therapies and multi-domain preventive trials such as those being tested in World-Wide FINGERS [ 62 , 63 ]. As such, 20% reduction of amyloid accumulation may be a relevant target to detect, especially in a short 1-year Proof-of-Concept study.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, other interventions may have more subtle effects on amyloid burden, either directly or indirectly. Some examples would be BACE1 inhibitors [ 60 ], drugs with other targets which have downstream amyloid effects [ 61 ], or non-pharmacological therapies and multi-domain preventive trials such as those being tested in World-Wide FINGERS [ 62 , 63 ]. As such, 20% reduction of amyloid accumulation may be a relevant target to detect, especially in a short 1-year Proof-of-Concept study.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, an international network of multidomain intervention clinical trials has been established to replicate the groundbreaking Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER), which demonstrated that a combination of lifestyle interventions reduces the risk of cognitive decline in older adults with vascular risk factors that increase their risk of dementia. The Worldwide FINGERS initiative (WW-FINGERS) provides a platform for investigators in different countries and cultures to adapt the FINGERS protocol while using similar protocols and sharing data ( 19 ).…”
Section: The Landscape Of Ad Platform Trialsmentioning
confidence: 99%
“…Mild cognitive impairment (MCI) is an etiologically heterogeneous syndrome characterized by memory performance below the age norm and represents a transitional state between normal aging and dementia disorders. Globally, efforts have been taken to explore neuroprotective effects of nutraceutical products among the aging population aiming for the prevention of neurodegenerative diseases such as dementia through food-based recommendations [ 7 , 8 , 9 , 10 ]. Asian in particular is rich in traditional herbs and vegetables potentially use as nutraceutical.…”
Section: Introductionmentioning
confidence: 99%